Botswana Labor Market Signals on Demand for Skills - World Bank (Washington, DC, 2015)
Botswana has an official unemployment rate of 17.8 percent. The low labor-intensity of growth is a potential explaining factor for this high level of unemployment. It is thus essential to analyze the role of education and training in the access to employment. This note finds that the role of education has changed under the effect of schooling expansion and persistent unemployment. Labor market institutions appear to have a limited impact on employment and wage levels, while the importance of active labor market programs is growing. This note aims to identify labor market signals that point to demand for specific current and future skills. The note seeks to answer the following questions: does the labor market place a higher premium on workers literacy and numeracy skills, technical skills, or behavioral skills?; is the labor market more in need of secondary or tertiary education graduates?; and will growing economic sectors (for example, tourism) benefit more by increasing the supply of sector-specific skills (for example, through specific training for tour guides and hospitality staff) or general skills (for example, through training of lawyers and accountants who can be absorbed in any sector of the economy)?.This note analyzes the following data and documentation to identify labor market signals in the Botswana economy: government economic growth and diversification strategies; general labor market data; and enterprise and employee surveys.